Quantitative microbiological risk assessment of L. monocytogenes in Blue mussel (Mytilus edulis) - Mufty, Murad, 1976- (2012)
Aims Mussels are generally regarded as high-risk products; they are likely to be contaminated with indigenous and non-indigenous pathogens and toxins. The aim of this study was to conduct a quantitative microbiological risk assessment (QMRA) of L. monocytogenes in the blue mussel (Mytilus edulis), following the guideline provided by Codex Alimentarius (1999). Methods The study was based on prevalence of illness (Listeriosis) and by consumer survey on blue mussel consumption in Iceland, also by collecting data on L. monocytogenes contamination in blue mussels and its environment, simulation and prediction of bacterial growth in the mussels. A quantitative risk assessment model was developed to assess the risk in healthy and susceptible population. Different assumptions were made to describe the variables of the model by probability distribution and mathematical models. Monte Carlo simulations of the model were run to estimate the number of cases in healthy and susceptible populations. Results Contradictory to results from abroad no L. monocytogenes were found in blue mussels collected locally in Iceland. Consumption of mussels in Iceland is low compared to other countries. From the three risk management measures simulated, shelf life reduction and hygiene improvement with triangle distribution for the both healthy and susceptible population groups was the most effective in reducing the number of cases of illness. Bases on research data, few risk management options were provided to minimize the defined risk. Conclusion This work showed that the risk of acquiring Listeriosis from the consumption of locally grown Blue mussels is minimal. The fresh Blue mussels were found save to consume however other hazards might pose other risks United Nations University-Fisheries Training Programme (http://www.unuftp.is/)